Human development index of rural communities in Malaysia: Tembeling, Pahang and Muar Rivers - Abu Samah, Asnarulkhadi; Md. Yassin, Sulaiman; Idris, Khairuddin; Abu Samah, Bahaman; Hamzah, Azimi; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2014)
This quantitative study attempts to determine, the Human Development Index (HDI) level of river communities in Malaysia. A total of 240 respondents were selected from 4 villages located near to Tembeling, Pahang and Muar Rivers. The analysis confirms that the HDI level of the respondents studied is low; however respondents in Gintong recorded a moderate-level HDI compared to other 3 areas which recorded low HDI values. Furthermore, there is a significant difference in terms of HDI between the 4 areas studied. Several strategies are suggested by which to further enhance the HDI of local communities, particularly those who reside near to rivers.